Exploring Gender Constructs in Media Narratives - Elharraki, Badia (ppjbsip, 2024)
This paper seeks to examine the discourse of women who have experienced marital violence as depicted in Moroccan media. Specifically, we will investigate how these women justify their discourse through authorization, aiming to construct arguments that portray them as victims and vilify their abusive husbands. Our analysis focuses on content from Medi 1TV, particularly the talk show